Effect of colloid on acid-base balance during colorectal surgery: balanced (tetraspan) versus non balanced (venofundin) hydroxyethyl starch - Ramly, Nur Fariza (IIUM Press, 2017)
This prospective, randomized, controlled study was carried out to compare the usage of balanced and non balanced hydroxyethyl starch during elective colorectal surgery in term of changes in acid-base balance and renal profile in the immediate and early postoperative period. Thirty informed, consented, adult patients with ASA I-II, undergoing open colorectal surgery with duration of more than three hours were recruited after excluding those with significant cardiac, liver or renal diseases, and those with allergy to the starches. These patients were randomly allocated into two study groups. The Balanced group received an intraoperative fluid regimen that consisted of Hartmann’s solution and balanced 6% hydroxytehyl starch (Tetraspan®). The Non Balanced group were given Hartmann’s solution and saline-based 6% hydroxyethyl starch (Venofundin®). Patients were kept hemodynamically stable and normovolumia throughout the operation by giving boluses of the study fluids as volume replacement therapy. Biochemical indices for acid base balance and renal profile were reviewed at two endpoints: immediately post operation (at 1-hour) and early post operation (at 6-hour). There were no difference at immediate and early post operation respectively, noted in term of base excess (p = 0.733 , p = 0.507 ) , chloride (p = 0.483, p = 0.401), lactate (p = 0.477, p = 0.993), urea (p = 0.244, p = 0.190) and creatinine (p = 0.578, p = 0.323) between both groups.